TAEP4.0: Teacher Assistance Educational Process Based in the Context of Education 4.0 - Silva, Deivid Eive; Sobrinho, Marialina Corrêa; Valentim, Natasha Malveira (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE); 2021: Anais Estendidos do X Congresso Brasileiro de Informática na Educação, 2021)
This dissertation presented an educational process to assist Basic Education teachers in preparing classes with technological resources, focusing on the skills and competencies necessary for Education 4.0 called TAEP4.0 (Teacher Assistance Educational Process). The ADDIE model was used to guide the development and evaluation of TAEP4.0 through studies. The results indicated that TAEP4.0 could increase teachers' knowledge and interaction with the characteristics of Education 4.0, such as integrating Computing and Informatics into classes and encouraging 21st-Century skills and competencies. In general, it is believed that TAEP4.0 can contribute to the advancement of Education 4.0, mainly in schools with few resource options.